On positive Cohen weakly nuclear multilinear operators - Bougoutaia, A.; Belacel, A.; Macedo, R.; Hamdi, H. (Carpathian Mathematical Publications, 2023)
In this article, we establish new relationships involving the class of Cohen positive strongly p-summing multilinear operators. Furthermore, we introduce a new class of multilinear operators on Banach lattices, called positive Cohen weakly nuclear multilinear operators. We establish a Pietsch domination-type theorem for this new class of multilinear operators. As an application, we show that every positive Cohen weakly p-nuclear multilinear operator is positive Dimant strongly p-summing and Cohen positive strongly p-summing. We conclude with a tensor representation of our class.